Long PCR products and PCR kits - Zhao, Hanxiao; Jia, Yukun; Yang, Xianyu (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
To amplify a DNA segment of 5 000 base pairs (5 kb) from genomic DNA of Chinese toad (Bufo gargarizans), several polymerase chain reactions (PCR) were carried out using 4 different PCR kits (Taq kit, PrimeSTAR MAX kit, LA Taq kit and LA Taq with GC Buffer kit), 3 different concentrations of genomic DNA from two individuals as templates (1 mg/ml, 0.1 mg/ml, 0.01 mg/ml), and a pair of specific primers. The results showed that PrimeSTAR MAX kit made the successful amplification from the second individual with the template concentrations of 0.1 mg/ml and 0.01 mg/ml, but not 1 mg/ml. In case of LA Taq kit, PCR products were detected from both individuals with templates of 1 mg/ml and 0.1 mg/ml, but not 0.01 mg/ml. However, neither Taq kit nor LA Taq with GC Buffer kit made PCR product no matter template concentrations and individuals. These results indicated the effects of PCR kit and template concentration on long PCR products, which give us suggestions to choose suitable PCR kits and adjustment of template concentrations when there is no amplification of long DNA segment.